2016
DOI: 10.1186/s12348-016-0091-2
|View full text |Cite|
|
Sign up to set email alerts
|

The role of oral co-trimoxazole in treating Nocardia farcinica keratitis—a case report

Abstract: Background Nocardia farcinica is one of the more recently identified species of the Nocardia genus. Nocardia farcinica keratitis is a rare occurrence, with only eight previously reported cases. Semi-permeable rigid contact lens use was associated with one of these reported cases. We report the first case of extended wear soft contact-lens-related Nocardia farcinica keratitis and recommend a new treatment regime.FindingsA 47-year-old lady presented with a right eye keratitis after wearing her extended wear soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Pulmonary disease is the most common presentation of Nocardia in immunosuppressed patients and approximately one-third of affected patients have a disseminated disease ( Ambrosioni et al, 2010 ; Kandi, 2015 ; Scorey and Daniel, 2016 ). Infection of traumatic wounds produces chronic inflammation that may lead to fistulas, abscesses, cellulitis, ulcerations, and mycetoma ( Smego and Gallis, 1984 ; Salinas-Carmona, 2000 ; Salinas-Carmona et al, 2009 ), and may extend into muscles, bones, the brain, kidneys, the prostate, cornea, heart, and adjacent organs ( De Nardo et al, 2013 ; Sirijatuphat et al, 2013 ; Kumar et al, 2014 ; Park et al, 2014 ; Sharma and O’Hagan, 2016 ). Nocordia infection of the central nervous system may be acquired by cutaneous or respiratory routes ( Smego and Gallis, 1984 ; Beaman and Beaman, 1994 ; Inamadar and Palit, 2003 ; Zakaria et al, 2008 ; Chen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary disease is the most common presentation of Nocardia in immunosuppressed patients and approximately one-third of affected patients have a disseminated disease ( Ambrosioni et al, 2010 ; Kandi, 2015 ; Scorey and Daniel, 2016 ). Infection of traumatic wounds produces chronic inflammation that may lead to fistulas, abscesses, cellulitis, ulcerations, and mycetoma ( Smego and Gallis, 1984 ; Salinas-Carmona, 2000 ; Salinas-Carmona et al, 2009 ), and may extend into muscles, bones, the brain, kidneys, the prostate, cornea, heart, and adjacent organs ( De Nardo et al, 2013 ; Sirijatuphat et al, 2013 ; Kumar et al, 2014 ; Park et al, 2014 ; Sharma and O’Hagan, 2016 ). Nocordia infection of the central nervous system may be acquired by cutaneous or respiratory routes ( Smego and Gallis, 1984 ; Beaman and Beaman, 1994 ; Inamadar and Palit, 2003 ; Zakaria et al, 2008 ; Chen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies and drug susceptibility results, N. farcinica is sensitive to compound sulfamethoxazole and amikacin, and resistant to cephalosporins, tobramycin and ciprofloxacin. [ 5 , 18 , 19 ] It has been reported that vitreous body injection of amikacin may lead to macular necrosis. [ 20 , 21 ] However, there are no effective antibiotics that can control infection through anterior chamber injection.…”
Section: Discussionmentioning
confidence: 99%
“…Of the few reports of N. farcinica eye infection, the therapeutic efficacy of mild keratitis is acceptable, while the efficacy for endophthalmitis is relatively poor. [ 3 5 ] In this study, we report a case of infectious scleritis involving the corneal limbus, which is suspected to be caused by N. farcinica in traumatic wound infection. The diagnosis was quickly and accurately confirmed by pathogenic microorganism culture and metagenomic sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Several antibiotics were implemented in the treatment of ocular Nocardiosis including topical chloramphenicol [27], gentamicin [42], polymyxin B sulfate/trimethoprim, amikacin, ciprofloxacin, levofloxacin, moxifloxacin, ofloxacin, gatifloxacin [28], tobramycin, and imipenem [15], and oral clarithromycin [17]. Resistance to tobramycin [43], ciprofloxacin [43], trimethoprim [44], vancomycin [19], clarithromycin [45], and amikacin [1,46] have been reported. Currently, amikacin is the treatment of choice for ocular Nocardiosis [45,46].…”
Section: Treatmentmentioning
confidence: 99%